Influence of seagrass traits on the diversity of endophytic fungi - VENUS B. KINAMOT (Society for Indonesian Biodiversity, 2024)
Abstract. Kinamot VB. 2024. Influence of seagrass traits on the diversity of endophytic fungi. Biodiversitas 25: 1254-1263. The interest in endophytic fungi has grown recently because of their potential to enhance plant growth, tolerate stresses, and modulate phytohormone synthesis. Understanding how plants influence their endophytic fungal assemblage is vital to manipulating them for biotechnological applications. In this study, Bray-Curtis analysis determined the variation of endophytic fungal assemblage among different seagrass species. Leaf/root area, leaf/root dry matter content, leaf mass per area, leaf toughness, and specific leaf area of seagrasses were measured using a standard protocol. The Folin-Ciocalteau method was utilized to quantify the phenolic and tannin contents in seagrasses using tannic acid as standard. Canonical correspondence analysis correlated the influence of seagrass traits on endophytic fungal diversity. Results showed that endophytic fungal diversity varied with seagrass hosts in which higher similarity of the fungal assemblage was observed among the same seagrass species than in different seagrass species. The seagrass traits mediated the variation of endophytic fungi. Phenolic and tannin in seagrasses significantly influenced the diversity of endophytic fungi. An antifungal assay using the methanolic crude extract of seagrasses had 80-100% mycelial growth inhibition to the five species of endophytic fungi tested, which could be accounted for the chemicals like phenol and tannin that the seagrass hosts produce.